Ramsar sites in the countries of the Balkan region and tourism development - G. Georgiev; M. Vasileva (Юг России: экология, развитие, 2015)
Wetlands are areas of special protection status due to their extraordinary significance for the preservation of some animal species and their natural habitats. Despite the fact that such territories preserve valuable animal and plant species, they remain unknown for the community and their resource potential is not used optimally. Based on the concept for sustainable tourism development, this paper offers a model for their recreational assimilation in comply with tourism purposes, especially through tourism development. Under analysis are the Ramsar sites in the countries of the Balkan peninsula. Some recommendations and conclusions are made on the basis of their assessment and unused resources.